House price changes, ripple effect and bank stability in Malaysia - Kok, Shiau Hui (2018)
Housing is one of the key sectors in an economy. Changes in the housing market have often led to an economic boom and then a downfall. Malaysia, as a developing economy, has experienced exponential growth in its housing market recently. We have had three objectives in forming our study. The first objective is to examine the ripple effect as it may relate to housing prices. The ripple effect, at least in theory, might be seen when increases in housing prices in some regions, such as the four most developed states in Malaysia, seem to cause housing prices in nearby regions to also increase. We have investigated the possible ripple effect in selected states in the central and northern regions of the country by means of the spatial vector autoregressive model. We have found that prices in Kuala Lumpur influence prices in Selangor and Negeri Sembilan and that prices in Penang influence prices in Perak and Kedah. The second objective is to investigate how the macroeconomic picture is reflected in housing price changes. It is essential to identify the economic factors that have significantly affected housing prices and the housing factors that have affected the economy. Our study argues that the relationship between housing prices, housing sales, and macroeconomic variables is, in fact, nonlinear. We have found that in the long run, the real effective exchange rate asymmetrically affects housing prices, whereas the estimated number of house sales responds more to positive changes in income. Imbalance in the residential market is often the underlying cause of a financial crisis. If the level of mortgage lending is high but the market begins to decline, banks could become unstable. The third objective is to examine the impact of changes in housing prices on bank stability in Malaysia by using the autoregressive distributed lag estimation. We see that an inverted-U–shaped relationship exists between housing prices and the Z-score, so that initially, banks are more stable when housing prices increase; banks become unstable after prices reach a certain extreme point. The relationship is significant in both the short and long run. Our study presents several findings that could affect economic policy. First, with regard to the ripple effect, we suggest that price movements in the most developed state should be the target for policymakers. Second, evidence in the macroeconomic picture shows that housing prices are sticky downward, and it is therefore essential to consider price stickiness in formulating policy. Third, our findings highlight the fact that banks become unstable after prices have risen above a certain point; once prices have “overheated,” policies for stabilizing the market may be needed.